Visual Structure Construction Of Mahabharata Series Illustrated Stories By Herjaka In Postmodern Perspective - Nuriarta, I Wayan; Ari, Ida Ayu Dwita Krisna (Jurnal Bahasa Rupa, 2025)
Picture stories are known as popular culture because of their mass production. In the view of modern art, picture stories are categorized as low-class work. However, with the presence of the literary heritage of the Mahabharata story in puppets, Herjaka's Mahabharata series becomes a paradox because the low-class and high-class cultures merge into one. This study aims to describe the construction of the visual structure of the Mahabharata series as a postmodern culture. This research method uses a qualitative design with data analysis using visual communication design theory, postmodern theory, representation theory, and hermeneutic theory. The results show that the construction of the visual structure of the Mahabharata series by Herjaka consists of modern and traditional visual appearances. This literary work is a postmodern cultural work because the fusion of boundaries between traditional and modern cultures and the loss of boundaries between literary heritage and popular culture marks it. The picture stories in the Mahabharata series show the birth of the re-creation of the picture stories and the presence of culture as a struggle for meaning in postmodern culture.